African American Patient Preferences for Glaucoma Education. Issue 4 (April 2017) - Sleath, Betsy; Davis, Scott; Sayner, Robyn; Carpenter, Delesha M.; Johnson, Terence; Blalock, Susan J.; Robin, Alan L.
ABSTRACT: Purpose: The objectives of the study were to examine (a) the types of questions that African American patients have about glaucoma for their providers and (b) how patients' sociodemographic characteristics are associated with where and from whom they would like to learn about glaucoma and glaucoma medications. Methods: Forty-nine adult African American patients with glaucoma were recruited at a private ophthalmology clinic where they completed a questionnaire for this cross-sectional study. Results: African American patients had a mean of 3.9 questions for their ophthalmologists; the questions that patients checked as having most often were "What is my prognosis with glaucoma?" (49%) and "What is my intraocular pressure?" (45%). Seventy-six percent of patients preferred that an educational program about glaucoma be offered at the doctor's office and 39% preferred it be offered at a community or senior citizen center. Ninety percent said that the education program should be offered by doctors. Patients under the age of 70 were significantly more likely to want a program on the Internet than patients age 70 and over (Pearson χ 2 = 4.7, P = .03). If an educational program was developed patients reported being most interested in the following topics, glaucoma medications (84%), what is glaucoma and what does it mean to have it? (83%). Conclusions: African American patients have many questions about glaucoma for their eye care providers. African American patients would prefer glaucoma educational programs be offered at their provider's office. Our findings could be used to develop educational programs for African American patients with glaucoma.